2013
DOI: 10.1111/acem.12282
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Pediatric Visits to the Emergency Department for Psychiatric Illnesses

Abstract: Objectives: While recent studies have demonstrated an overall increase in psychiatric visits in the emergency department (ED), none have focused on a nationally representative pediatric population. Understanding trends in pediatric psychiatric ED visits is important because of limited outpatient availability of pediatric specialists, as well as long wait times for psychiatric appointments. The study aim was to evaluate the trends in ED psychiatric visits for children between 2001 and 2010 with comparison by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
106
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 32 publications
14
106
2
1
Order By: Relevance
“…Also, they reported that the most frequent disorders in adolescence were psychoactive substance use disorders (25.2%) for boys and mood disorders (33.6%) for girls. In a large, nationally representative ED database including data from 2001 to 2011, the most common primary ICD-9 diagnoses were anxiety states/panic disorder (14%) and depression (13%) (15). The rate of conduct disorder in our sample was higher than the rates of conduct or disruptive disorders (range 6.3-14%) found in other studies conducted at universities or general hospitals (9,10,13,20,32,33).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Also, they reported that the most frequent disorders in adolescence were psychoactive substance use disorders (25.2%) for boys and mood disorders (33.6%) for girls. In a large, nationally representative ED database including data from 2001 to 2011, the most common primary ICD-9 diagnoses were anxiety states/panic disorder (14%) and depression (13%) (15). The rate of conduct disorder in our sample was higher than the rates of conduct or disruptive disorders (range 6.3-14%) found in other studies conducted at universities or general hospitals (9,10,13,20,32,33).…”
Section: Discussioncontrasting
confidence: 61%
“…Pediatric EDs have been shown to serve as an entry point into the healthcare system for children and adolescents seeking psychiatric care and are considered a safe area for the lack of inpatient and outpatient mental health services (7,9). Several studies reported a marked increase in the number of children and adolescents seeking care for mental health problems in emergency settings (10)(11)(12)(13)(14)(15). Also, the prevalence of mental health problems in pediatric EDs has been found to be much higher (1).…”
Section: Introductionmentioning
confidence: 99%
“…During the study period BH-related ED visits for children rose (32, 33). Evidence also suggests that psychotropic medication use and outpatient mental health treatment for children increased between 1996-1998 and 2010-2012 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that 3–8 % of pediatric mental health ED presentations in the United States and Canada are for psychotic symptoms [1114]. ED visits are considered an important contact point to reduce the duration of untreated psychosis through assessment and referral to early intervention programs [5, 15, 16].…”
Section: Introductionmentioning
confidence: 99%